The Effect of Gel-Electrolyte on Dye Sensitized Solar Cell (DSSC) Prototype based on Nanosized-TiO2 Using Mangosteen Pericarp as Absorber - Kumila, Biaunik Niski; Prajitno, Gontjang (Journal Of Natural Sciences And Mathematics Research, 2017)
Dye Sensitized Solar Cell (DSSC) with Fluorine deped Tin Oxide (FTO) substrat and nanosize-TiO2 layer sensitized by âdyeâ ,mangosteen pericarp extract, was succesfully fabricated. Gel-Electrolyte as electron regenerator was synthesized by adding Polyethylene Glycol (PEG) 1000 to electrolyte solution while nanosize-TiO2 was synthesized by co-precipitation method from TiCl3 solution. The crystal size of TiO2 characterized by X-Ray Diffraction is 10.5 nm in size. The solar absorbance of âdyeâ mangosteen pericarp was measured using UV-Vis Spectrophotometer and it showed that the dye can absorb photon at Near Ultraviolet (NUV) to yellow visible light. Nanosize-TiO2 based DSSC with gel-electrolyte successfully reached short circuit current up to 30.9 Î¼A, open circuit voltage 398.3 mV and performed the long term stability. Â©2017 JNSMR UIN Walisongo. All rights reserved